A morphological and molecular study in the Deschampsia cespitosa complex (Poaceae; Poeae; Airinae) in northern North America - Chiapella, Jorge Oscar; DeBoer, Verónica; Amico, Guillermo Cesar; Kuhl, Joseph (American Journal of Botany)
Premise of the study: In the North American Arctic, the existence of one or several taxa closely related to Deschampsia cespitosa var. cespitosa has remained a puzzle for many years. Extreme morphological variation, lack of clear limits between alleged forms, and an extended geographic range often render identification keys incomplete, and raise the question of how many species this taxon represents. Methods: Morphological and molecular analysis, including multivariate statistics, ITS and the cpDNA marker trnK-rps16, was conducted on D. cespitosa var. cespitosa and related taxa using 201 herbarium specimens from northern North America (Alaska, Canada, and Greenland). Fifty-three morphological centeracters were recorded from all specimens, while sequences were retrieved from 167 specimens. Key results: Results show that Deschampsia cespitosa (L.) P. Beauv. var. cespitosa, D. cespitosa subsp. alpina (L.) Tzvelev, D. cespitosa subsp. beringensis (Hultén) W. E. Lawr., D. brevifolia R. Br., D. cespitosa (L.) P. Beauv. subsp. glauca (Hartm.) C. Hartm., D. mackenzieana Raup, D. cespitosa subsp. orientalis Hultén, and D. pumila (Griseb.) Ostenf. differed significantly in a few morphological variables, but molecularly are a closely related group with several sequences and haplotypes that are nearly identical. Conclusions: Overall, the evidence points to the existence of a single species, Deschampsia cespitosa. The occurrence of slightly different morphological types related to specific geographical distributions allows recognition of three additional taxa at the infraspecific level, D. cespitosa subsp. alpina, D. cespitosa subsp. beringensis, and D. brevifolia. All studied taxa showed morphological variation in a gradient, suggesting the existence of phenotypic plasticity. Fil: Chiapella, Jorge Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Córdoba. Instituto Multidisciplinario de Biología Vegetal (p); Argentina. Universidad Nacional de Córdoba; Argentina Fil: DeBoer, ...